Effectiveness of the Continuing Motivational Interviewing Telephone-Based Enhancing Program Among Persons with Alcohol Use Disorders, Thanyarak Chiangmai Hospital - Boonart, Nutthawee; Skulphan, Sombat; Wannachaiyakul, Saranya (Journal of The Royal Thai Army Nurses, 2026)
This study was implementation research to study the Effectiveness of the Continuing Motivational Interviewing Telephone-Based Enhancing Program Among Persons with Alcohol Use Disorders, Thanyarak Chiangmai Hospital Operated under the framework of Roger’s innovation diffusion theory. 2 specific groups were selected as participants: 1) 15 persons with alcohol use disorders and 2) 5 health personnel. The research instruments included 1) the Continuing Motivational Interviewing Telephone-Based Enhancing Program Among Persons with Alcohol Use Disorders, 2) the Alcohol Consumption Assessment (ACA), 3) a satisfaction assessment form for people with alcohol use disorders and 4) a form for evaluating the opinions of the health personnel team. The analysis was performed using descriptive statistics, including frequency distribution, mean, and standard deviation. The study results found that those with alcohol use disorders had a 100% reduction in their drinking behavior scores and were able to stop drinking alcohol, 53.33%. And 100% of the participants were satisfied with the program and found it beneficial to themselves, their relatives or caregivers and found it convenient to receive care according to the program. As for the health personnel team, 100% agreed that the program is useful for caring for people with alcohol use disorders. The program can be integrated with existing knowledge, is easy to implement, and the results are clearly visible. It can be seen that this program can effectively reduce drinking behavior.